2019
DOI: 10.1158/1940-6207.capr-18-0317
|View full text |Cite
|
Sign up to set email alerts
|

Testing Novel Pyrimidinyl Rexinoids: A New Paradigm for Evaluating Rexinoids for Cancer Prevention

Abstract: Rexinoids, selective ligands for retinoid X receptors (RXR), have shown promise in preventing many types of cancer. However, the limited efficacy and undesirable lipidemic side-effects of the only clinically approved rexinoid, bexarotene, drive the search for new and better rexinoids. Here we report the evaluation of novel pyrimidinyl (Py) analogues of two known chemopreventive rexinoids, bexarotene (Bex) and LG100268 (LG268) in a new paradigm. We show that these novel derivatives were more effective agents th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…have confirmed that the iNOS assay correlates with in vivo efficacy 21 , few investigators have used the induction of SREBP in vitro as a biomarker to predict the ability of novel rexinoids to increase triglycerides in vivo. Elevated triglycerides are a side-effect found with many RXR agonists in preclinical models and by bexarotene in humans 13,14 .…”
Section: Rexinoids Upregulate the Expression Of Srebp In Liver Cells mentioning
confidence: 99%
See 3 more Smart Citations
“…have confirmed that the iNOS assay correlates with in vivo efficacy 21 , few investigators have used the induction of SREBP in vitro as a biomarker to predict the ability of novel rexinoids to increase triglycerides in vivo. Elevated triglycerides are a side-effect found with many RXR agonists in preclinical models and by bexarotene in humans 13,14 .…”
Section: Rexinoids Upregulate the Expression Of Srebp In Liver Cells mentioning
confidence: 99%
“…Elevated triglycerides are a side-effect found with many RXR agonists in preclinical models and by bexarotene in humans 13,14 . In order to validate the utility of SREBP as an in vitro biomarker for increased triglycerides in vivo, established rexinoids known to induce hypertriglyceridemia (bexarotene, LG100268, and IRX194204) and LG101506 (a rexinoid that does not induce hypertriglyceridemia in vivo) 21,42 were directly compared to evaluate their ability to induce SREBP protein in vitro ( Fig. 1A).…”
Section: Rexinoids Upregulate the Expression Of Srebp In Liver Cells mentioning
confidence: 99%
See 2 more Smart Citations
“…Bexarotene, a RXR stimulator, has been applied in the treatment of cutaneous T‐cell lymphoma. Bexarotene can stimulate the apoptosis of tumor cells and plays an immunomodulatory role, especially in the aspect of reducing macrophages in the tumor microenvironment …”
Section: Discussionmentioning
confidence: 99%